Efektivitas Modul Pencemaran Sampah dengan Model Argument-Driven Inquiry (ADI) untuk Meningkatkan Keterampilan Berpikir Kritis Mahasiswa Biologi - Diartika, Eka Imbia Agus (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Critical thinking skills are a crucial aspect of the 21st century, playing a fundamental role in various areas of life, yet they are still not optimally developed in classrooms. This research aims to develop critical thinking skills through the Argument Driven Inquiry (ADI) module for biology students. This study uses a nonrandomized control-group pretest-posttest design experiment involving three classes as the experimental group, positive control, and negative control. This research sample consisted of 67 biology students from Universitas Negeri Malang across three classes. Data collection techniques employed pretest and posttest questions on critical thinking skills. Data analysis was performed using ANCOVA. The results of the ANCOVA test on the biology students' critical thinking revealed a significance of learning at 0.036 (less than 0.05), thus it can be concluded that the research hypothesis is accepted, indicating a difference in critical thinking between students using the ADI module, ADI model, and PowerPoint. The ADI module proved effective in enhancing the critical thinking skills of biology students, with significantly higher posttest results compared to other learning models. The development of this module also included the integration of interactive videos about the conditions of garbage mountains and leachate water pollution at the Supit Urang Malang landfill, providing a more realistic context for the students